EXPLORING PARENTS' EXPOSURE OF ENGLISH TO THEIR CHILDREN: AN EYL STUDY IN THE CONTEXT OF YOGYAKARTA - Andi Hidayat Thamrin; Ziaul Haq; Riris Handayani (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study investigates how parents in a Yogyakarta elementary school expose English to their children through qualitative interviews with 10 participants. The findings reveal a highly positive attitude among parents toward nurturing English proficiency in their children. Motivated by the global importance of English, parents actively establish a supportive environment for language development. They aim for early English mastery, employing a bilingual approach at home. Engaging in diverse activities such as watching English films and reading books, parents create a language-rich environment, ensuring positive experiences. Witnessing tangible progress, parents express confidence in the benefits of early language exposure and are dedicated to fostering a positive English language learning atmosphere, encouraging courage in language attempts and accepting mistakes. Keyword: early English proficiency, English language exposure, parental involvement. Abstrak: Penelitian ini menyelidiki bagaimana orang tua di sebuah sekolah dasar di Yogyakarta memperkenalkan bahasa Inggris kepada anak-anak mereka melalui wawancara kualitatif dengan 10 partisipan. Temuan penelitian ini menunjukkan sikap yang sangat positif di antara para orang tua dalam mengembangkan kemampuan berbahasa Inggris pada anak-anak mereka. Termotivasi oleh pentingnya bahasa Inggris secara global, para orang tua secara aktif membangun lingkungan yang mendukung perkembangan bahasa. Mereka bertujuan untuk penguasaan bahasa Inggris sejak dini, dengan menggunakan pendekatan bilingual di rumah. Terlibat dalam berbagai kegiatan seperti menonton film berbahasa Inggris dan membaca buku, para orang tua menciptakan lingkungan yang kaya akan bahasa, memastikan pengalaman yang positif. Menyaksikan kemajuan yang nyata, para orang tua mengungkapkan keyakinan mereka akan manfaat paparan bahasa sejak dini dan berdedikasi untuk membina suasana belajar bahasa Inggris yang positif, mendorong keberanian dalam upaya berbahasa dan menerima kesalahan. Kata kunci: kemahiran Bahasa Inggris sejak dini, keterlibatan orang tua, paparan Bahasa Inggris.